2015
DOI: 10.1088/0031-9155/60/3/1259
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sensitivity of the optimization of acquisition geometry to the choice of reconstruction algorithm in digital breast tomosynthesis through a simulation study

Abstract: Due to the limited number of views and limited angular span in digital breast tomosynthesis (DBT), the acquisition geometry design is an important factor that affects the image quality. Therefore, intensive studies have been conducted regarding the optimization of the acquisition geometry. However, different reconstruction algorithms were used in most of the reported studies. Because each type of reconstruction algorithm can provide images with its own image resolution, noise properties and artifact appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 55 publications
(76 reference statements)
3
55
0
Order By: Relevance
“…For all three phantom variants, simulated images were generated for both mammography and DBT using a previously reported projection and FBP reconstruction algorithm. [39] The resulting images were analyzed for anatomical realism using two techniques, power law slope and Laplacian fractional entropy.…”
Section: Quantitative Evaluationmentioning
confidence: 99%
“…For all three phantom variants, simulated images were generated for both mammography and DBT using a previously reported projection and FBP reconstruction algorithm. [39] The resulting images were analyzed for anatomical realism using two techniques, power law slope and Laplacian fractional entropy.…”
Section: Quantitative Evaluationmentioning
confidence: 99%
“…As various reconstruction algorithms have been developed for DBT, it is desirable to know whether the use of a different reconstruction algorithm would alter the optimal geometry associated with the current algorithm. We have previously investigated this problem by conducting an in silico imaging trial with digital breast phantoms, simulated DBT system with various reconstruction algorithms, and a computational model observer for image quality evaluation (Zeng et al 2015). System optimization was based on lesion detectability in a location-known task for a Laguerre–Gauss (LG) channelized model observer (CHO).…”
Section: Introductionmentioning
confidence: 99%
“…Possible sources of discrepancies between different model observer implementations were examined by Young et al 10 who showed the need to take interprojection correlations into account when applying the CHO in the projection domain and by Park et al 11 who demonstrated that the choice of different 2D and 3D observer channels resulted in different preferences in system geometry. Focusing on the evaluation of 3D reconstruction techniques, Van de Sompel et al 12 used the CHO to compare variants of filtered backprojection (FBP), the simultaneous algebraic reconstruction technique (SART), and maximum likelihood (ML) reconstruction, while Zeng et al 13 found that the choice of reconstruction method did not influence the ranking of different acquisition geometries.…”
Section: Introductionmentioning
confidence: 99%